2013
DOI: 10.1155/2013/680414
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Aging during Chronic Oxidative Stress: A Role for PARP-1

Abstract: Oxidative stress plays a major role in the pathophysiology of chronic inflammatory disease and it has also been linked to accelerated telomere shortening. Telomeres are specialized structures at the ends of linear chromosomes that protect these ends from degradation and fusion. Telomeres shorten with each cell division eventually leading to cellular senescence. Research has shown that poly(ADP-ribose) polymerase-1 (PARP-1) and subtelomeric methylation play a role in telomere stability. We hypothesized that PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 64 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…In blood cells, biological age predicted by DNA methylation status rather than chronological age is well correlated more with telomere length shortening and acquired aplastic anemia or dyskeratosis congenita - two diseases associated with progressive bone marrow failure [32]. The link between telomere shortening and subtelomeric DNA methylation was also confirmed in vitro using human fibroblasts cultured under conditions of chronic oxidative stress, induced by tert-butyl hydroperoxide [33]. Together with link between H. pylor i related PCGI methylation and telomere shortening in the stomach, it is suggested that alteration of telomere shortening and DNA methylation predict various pathological state and clinical outcomes across the different tissue types.…”
Section: Discussionmentioning
confidence: 99%
“…In blood cells, biological age predicted by DNA methylation status rather than chronological age is well correlated more with telomere length shortening and acquired aplastic anemia or dyskeratosis congenita - two diseases associated with progressive bone marrow failure [32]. The link between telomere shortening and subtelomeric DNA methylation was also confirmed in vitro using human fibroblasts cultured under conditions of chronic oxidative stress, induced by tert-butyl hydroperoxide [33]. Together with link between H. pylor i related PCGI methylation and telomere shortening in the stomach, it is suggested that alteration of telomere shortening and DNA methylation predict various pathological state and clinical outcomes across the different tissue types.…”
Section: Discussionmentioning
confidence: 99%
“…The complete study was performed with 114 patients, including 62 women with VI during pregnancy and 52 control women without evidence of VI during pregnancy. The mean age is 33 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] VI and 34 [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] HC. Not exist significant differences in the mean age of patients (P = .06915).…”
Section: Clinical and Demographic Characteristicsmentioning
confidence: 99%
“…53,54 Oxidative stress severely impairs cellular metabolism that involves mitochondrial function, and it damages molecules such as DNA. 32,55,56 The critical metabolism regulator iNOS is expressed in conditions of cellular oxidative stress. 19,52 We have observed the selective overexpression of iNOS in syncytiotrophoblast cells from the placentas of women with pregnancy-associated VI.…”
Section: Foetuses Of Mothers With Pregnancy-associated VI Show a Dementioning
confidence: 99%
See 2 more Smart Citations